Design of Data Acquisition System for Green Laser Photoacoustic Spectroscopy Using Audacity Software - Rakhmadi, Frida Agung; Mitrayana, Mitrayana; Pangestu, Gilang Kurniawan Dian (Proceeding International Conference on Science and Engineering, 2019)
Research on design of data acquisition system for green laser photoacoustic spectroscopy has been done. The purpose of this research was to create and test data acquisition system for green laser photoacoustic spectroscopy. The system was created with ATR 3350iS microphone as signal detector and audacity software as data recording and processing. The testing was conducted in four phases, firstly testing the system without laser, secondly testing the system with non-modulated laser, thirdly testing the system with modulated laser without a sample, and finally testing the system with modulated laser to wood sample. The result showed that there weren not any photoacoustic signals detected in condition of without laser and with non-modulated laser. Meanwhile, in the condition of modulated laser without sample and with the sample of wood, the data acquisition system detected photoacoustic signals in the range of laser modulation frequency was 1000 – 9981 Hz.